(untitled) (Journal of Applied Learning and Teaching, 2021)
There is a commonly held perception that when students are motivated toward learning, finding it engaging and relevant, they experience academic success. This message, echoed loudly in Australian society, anywhere from researchers to social commentators; reflects a call for Australian educators to make content and learning experiences sufficiently appealing to students, thus providing the greatest opportunity for academic success. As a result, a trend toward student-centred learning routines, where learning is designed in accordance with what students deem interesting and relevant, is becoming increasingly popular in Australian primary school classrooms (6-12 year old students). This task can be confusing and daunting for teachers. In our current fast-paced, technology driven world, how does one make lessons about prepositions, the Cartesian plane or vowel alternations interesting enough to incite motivation and enthusiasm for learning? Or, could it be that academic achievement and student motivation is less influenced by an individual’s personal interest in a learning task or domain, and more about what the teacher does to establish learning routines that enhance these factors for students? Findings of this study propose that the way teachers establish effective learning routines has more influence on student motivation and academic achievement than the extent to which students might initially consider content engaging or relevant. The findings contribute toward the existing body of knowledge relating to teacher-led learning routines, academic achievement and student motivation in the Australian primary school context. While findings do not mandate an either/or position when considering teacher-led or student-centred instruction, educators are urged not to neglect teacher-led learning routines in the Australian primary school classroom. As such, pre-service teacher education and training should reflect accordingly.